2018
DOI: 10.1002/adhm.201800695
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed In Vivo Imaging Using Size‐Controlled Quantum Dots in the Second Near‐Infrared Window

Abstract: PbS/CdS core/shell quantum dots (QDs) that emit at the second near‐infrared (NIR‐II, 1000–1700 nm) window are synthesized. The PbS seed size and CdS shell thicknesses are carefully controlled to produce bright and narrow fluorescence that are suitable for multiplexing. A polymer encapsulation yields polymer‐encapsulated NIR‐II QDs (PQDs), which provides the QDs with long‐term fluorescence stability over a week in biological media. Exploiting the simple bioconjugation capability of PQDs, folic acids are conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The emergence and development of new technologies have led to novel fluorescent nanoparticles emitting in the second NIR window (NIR-II, 1,000–1,700 nm), which allows NIRF imaging to visualize deep tissues with an unprecedented degree of clarity for diagnosis or surgical guidance. 100 , 101 , 102 , 103 Some novel biofunctionalized NIR-II nanoparticles, such as quantum dots (QDs), 56 , 104 , 105 single-walled carbon nanotubes (SWNTs), 106 , 107 and rare earth-based upconversion nanoparticles (UCNPs), 108 , 109 , 110 have been reported for the in vivo imaging of atherosclerosis or AMI, which will help to expedite the clinical transition of NIR imaging. Although differentiating vulnerable plaques from stable plaques remains challenging in the clinic, Gao et al.…”
Section: Nanotechnology Approaches To Detect Cadsmentioning
confidence: 99%
“…The emergence and development of new technologies have led to novel fluorescent nanoparticles emitting in the second NIR window (NIR-II, 1,000–1,700 nm), which allows NIRF imaging to visualize deep tissues with an unprecedented degree of clarity for diagnosis or surgical guidance. 100 , 101 , 102 , 103 Some novel biofunctionalized NIR-II nanoparticles, such as quantum dots (QDs), 56 , 104 , 105 single-walled carbon nanotubes (SWNTs), 106 , 107 and rare earth-based upconversion nanoparticles (UCNPs), 108 , 109 , 110 have been reported for the in vivo imaging of atherosclerosis or AMI, which will help to expedite the clinical transition of NIR imaging. Although differentiating vulnerable plaques from stable plaques remains challenging in the clinic, Gao et al.…”
Section: Nanotechnology Approaches To Detect Cadsmentioning
confidence: 99%
“…The researchers synthesized probes with 1080 and 1280 nm emission from 4.2 and 5.1 nm PbS seeds, demonstrating the feasibility of emission spectral tuning through size control. [70] Liu et al reported trialkylphosphine-controlled growth of Ag 2 Te QDs and achieved emission wavelength from 950 to 2100 nm. [50] It is because the coordination between trialkylphosphine and the Ag ion is stronger than that of 1-octanethiol, and thus the precise size control of Ag 2 Te QDs can be achieved.…”
Section: Bandgap and Structure Engineeringmentioning
confidence: 99%
“…Multiplexed bioimaging enables the simultaneous analysis of multiple targets and thus has strong potential for applications in real‐time observation of living biological and physiological processes and in clinical practice for noninvasive diagnostics, image‐guided surgery, etc. Kim et al [ 85 ] fabricated bright and narrow PbS/CdS QDs with different emission wavelengths by adjusting the size and accurately evaluated the active ligand‐assisted tumor targeting ability and passive tumor accumulation effect by two‐color imaging. Chen et al [ 27 ] used dual probes, IR‐FD, and PbS QDs for dual‐color imaging in NIR‐IIa and NIR‐IIb, enabling high‐precision observation of micrometastases in lymph nodes.…”
Section: Opportunitiesmentioning
confidence: 99%